Studies on Engineering Properties of Selected Natural Exudate Gums - Sharma, S. C.; Prasad, N.; Pandey, S. K.; Kar, Amit K. (Journal of Agricultural Engineering, 2018)
Selected engineering properties as colour parameters, moisture content, bulk density, true density, porosity, angle of repose and angle of internal friction of different exudate gums obtained from selected tree species were determined. Lightness, redness and yellowness values of exudate gums ranged from 22.66 – 49.58, 2.66 – 7.16 and 5.32 – 18.43, respectively. Moisture content, bulk density, true density, porosity and angle of repose of exudate gums ranged from 9.25 – 20.39 %, 592.5 – 792.78 kg.m-3, 1106.67 – 1430 kg.m-3, 36.75 – 49.81 % and 30.00 – 45.000, respectively. Angle of internal friction ranged from 24.520 to 29.050 for wood, 25.300 to 28.260 for glass, 25.020 to 29.280 for steel, 25.120 to 28.990 for galvanized iron, 25.450 to 27.860 for aluminium, 25.160 to 29.930 for mild steel, 26.450 to 28.580 for plywood, 24.970 to 27.990 for fibre, 24.980 to 27.440 for plastic and 20.980 to 27.970 for white board surfaces, respectively. Values of engineering properties determined under the study can be used as references in design of gum handling and processing machineries.